If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + -1x) + 7 = 2x + -4(x + -4) (3 * 2 + -1x * 2) + 7 = 2x + -4(x + -4) (6 + -2x) + 7 = 2x + -4(x + -4) Reorder the terms: 6 + 7 + -2x = 2x + -4(x + -4) Combine like terms: 6 + 7 = 13 13 + -2x = 2x + -4(x + -4) Reorder the terms: 13 + -2x = 2x + -4(-4 + x) 13 + -2x = 2x + (-4 * -4 + x * -4) 13 + -2x = 2x + (16 + -4x) Reorder the terms: 13 + -2x = 16 + 2x + -4x Combine like terms: 2x + -4x = -2x 13 + -2x = 16 + -2x Add '2x' to each side of the equation. 13 + -2x + 2x = 16 + -2x + 2x Combine like terms: -2x + 2x = 0 13 + 0 = 16 + -2x + 2x 13 = 16 + -2x + 2x Combine like terms: -2x + 2x = 0 13 = 16 + 0 13 = 16 Solving 13 = 16 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3(h+4)+5=35 | | (1+x)(1+z)= | | 10x^2+1210=0 | | 2ydx-2xdy=0 | | 18i-14i= | | 5x+-6+2=7x+-6 | | .6k-(k+.25)=.05(k+1) | | Z-4z=9z-9-z | | 2(5-2v)=5(v-5) | | 87-n=13 | | 24n^3+30n^2=0 | | -21a+28a-6=10 | | 4[(12+5)-1024]= | | 5y-15+6=5y+8-1x+17 | | 4x^2+6x+1=2x^2+6x-6+1 | | 8p+5-3=9+7p | | 3(d-2)=15 | | 3s+5w=19 | | 5x-54+3x+16=180 | | 2x^2=x^2-6 | | -4y=-x+6+zy | | 16x^4+32x^3+24x^2+8x-80=0 | | tan(x)=-0.364+0.57735027 | | 6-3u=21 | | n-6=13-4 | | 5-3(2x-4)=5(4x+2)-32 | | 80+.10x=132 | | 4x+48=828 | | (x^2-200x+4000log(x)-7200)=0 | | X+12y=23 | | -3a-7a=-3a-6a+7 | | 8u+2-4(-3u+2)=4(u-1) |